2016
DOI: 10.1007/s11695-016-2297-7
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Gut Microbiota After Roux-en-Y Gastric Bypass and Sleeve Gastrectomy in Sprague-Dawley Rats

Abstract: RYGB, but not SG, alters the gut microbiota of Sprague-Dawley rats. RYGB also reduces the diversity of gut microbiota. Furthermore, the abundance of Gammaproteobacteria negatively correlates with postoperative body weight and may be one of the potential contributors to stable weight loss after bariatric surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
72
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(86 citation statements)
references
References 34 publications
11
72
1
2
Order By: Relevance
“…Previous clinical studies have shown clear alterations in the microbiota associated to these treatments, especially in Proteobacteria (such as E. coli ) (Zhang et al, 2009; Furet et al, 2010; Kong et al, 2013; Tremaroli et al, 2015; Palleja et al, 2016). Evidence in animal models indicate a similar pattern of microbiota alteration (Liou et al, 2013; Shao et al, 2016). In concordance with previous studies, an important increase in Proteobacteria in RYGB and SG was observed in this study.…”
Section: Discussionmentioning
confidence: 95%
“…Previous clinical studies have shown clear alterations in the microbiota associated to these treatments, especially in Proteobacteria (such as E. coli ) (Zhang et al, 2009; Furet et al, 2010; Kong et al, 2013; Tremaroli et al, 2015; Palleja et al, 2016). Evidence in animal models indicate a similar pattern of microbiota alteration (Liou et al, 2013; Shao et al, 2016). In concordance with previous studies, an important increase in Proteobacteria in RYGB and SG was observed in this study.…”
Section: Discussionmentioning
confidence: 95%
“…Considering that systemic administration of ghrelin increases brain MOR mRNA expression in rats (Skibicka et al, 2012), it is possible that the RYGB-mediated lowering in plasma ghrelin contributes to reduced brain MOR levels postoperatively. Profound changes in gut microbiota also take place after RYGB in humans and rodents (Furet et al, 2010; Liou et al, 2013; Shao et al, 2016). Interestingly, secreted proteins from gut E. coli have been found to influence brain opioidergic feeding circuits (Breton et al, 2016) and may too underlie altered brain MOR signaling after RYGB.…”
Section: Discussionmentioning
confidence: 99%
“…Similar gut microbial changes were seen after non-surgical weight loss [112,118]. Unlike in non-surgical weight loss, there was an increased abundance of Proteobacteria, specifically Escherichia coli, after RYGB [115][116][117][119][120][121][122][123]. Enterobacteriaceae and Pasteurellaceae were also associated with weight loss after RYGB [122,123].…”
Section: Intestinal Motility After Rygbmentioning
confidence: 53%
“…Unlike in non-surgical weight loss, there was an increased abundance of Proteobacteria, specifically Escherichia coli, after RYGB [115][116][117][119][120][121][122][123]. Enterobacteriaceae and Pasteurellaceae were also associated with weight loss after RYGB [122,123]. Finally, compared to obese microbiota, RYGB gut microbiota transplant into germ-free mice led to weight loss and improved glucose tolerance [117,124,125].…”
Section: Intestinal Motility After Rygbmentioning
confidence: 97%